Model Aplikasi Game Edukasi Mengenal Sayuran dan Buah - Abidah, Siti; Handayani, Tia Selvina; Ariannor, Wahyudi (STMIK Banjarbaru, 2024)
Delivery of learning by conventional means of introducing vegetables and fruits in the early childhood environment has not succeeded in achieving the desired learning targets because some vegetable and fruit objects are difficult to find in the surrounding environment. An educational game application model to get to know vegetables and fruit based on Android will be applied to the teaching and learning process. The Multimedia Development Life Cycle method is used to develop the system. System design uses the Unified Modeling Language (UML) modeling tools, while system development uses the Android Studio IDE, and functional testing uses the Blackbox test. The results of functional testing state that all functional features run well in accordance with the functions and needs of the user. An Android-based educational game application model to get to know vegetables and fruit helps teachers in children's cognitive learning to provide an understanding of the benefits of vegetables and fruit and can attract interest in learning and have a positive impact on increasing children's natural intelligence.Keywords: Learning interest; Early childhood; Cognitive learning; Android; GameÂ AbstrakPenyampaian pembelajaran dengan cara konvensional pengenalan sayur-sayuran dan buah-buahan di lingkungan anak usia dini belum berhasil mencapai target pembelajaran yang diinginkan disebabkan beberapa objek sayuran dan buah sulit ditemui di lingkungan sekitar. Model aplikasi game edukasi mengenal sayuran dan buah berbasis andorid, akan diterapkan untuk proses belajar mengajar. Metode Multimedia Development Life Cycle digunakan untuk mengembangkan sistem. Desain sistem menggunakan tools pemodelan Unified Modelling Language (UML), sedangkan pembangunan sistem dengan IDE Android Studio, serta pengujian fungsional dengan uji Blackbox. Hasil pengujian fungsional menyebutkan bahwa semua fitur fungsional berjalan dengan baik sesuai dengan fungsi dan kebutuhan pengguna. Model aplikasi game edukasi mengenal sayuran dan buah berbasis andorid membantu guru dalam pembelajaran kognitif anak untuk memberi pemahaman mengenai manfaat dari sayuran dan buah, serta dapat menarik minat belajar dan berdampak positif meningkatkan kecerdasan natural anak-anak.Â